Pengaruh Disiplin Kerja dan Keselamatan Kesehatan Kerja (K3) terhadap Kinerja Satgas Penyapuan Jalan Rayon Kebersihan Selatan 1 Dinas Lingkungan Hidup Kota Surabaya - Sutarno, Sutarno; Artanti, Yessy (Al Makki Publisher, 2025)
The performance of the road sweeping task force is the result of employee work achieved by meeting the criteria and deadlines that have been set. Some of the factors that affect performance include discipline and occupational health and safety (K3). This study aims to analyze discipline and occupational health and safety (K3) on the performance of the sweeping task force. This study aims to analyze discipline and occupational health and safety (K3) on the performance of the sweeping task force. This study uses quantitative research. The sampling technique used was purposive sampling with a total of 55 respondents. The distribution was carried out offline by measuring answers using a linkert scale score of 1-5. The analysis used was multiple linear regression analysis. The results of this study show that work discipline has a significant influence on the performance of the road sweeping task force. whereas occupational health and safety (OHS) does not have a significant effect on the performance of the task force for sweeping the southern cleanliness rayon road 1 of the Surabaya City Environment Agency.